A systematic scoping review and textual narrative synthesis of physical and mixed‐reality simulation in pre‐service teacher training. (4th March 2022) - Ade‐Ojo, Gordon O.; Markowski, Marianne; Essex, Ryan; Stiell, Marlon; Jameson, Jill
Abstract: Background: Due to recent lockdown conditions, which restricted opportunities for face‐to‐face contact and the ability to be physically in schools, the need for novel, safe ways to train pre‐service teachers emerged even more pressingly. Whilst virtual simulation has received some attention in pedagogy and its benefits have been demonstrated in many disciplines, there appears to be less synthesized evidence on the use of physical and/or mixed‐reality simulation utilized in teacher training. Objectives: The goal of this systematic scoping review was to summarize and synthesize the literature on the use of physical and/or mixed‐reality simulation in pre‐service teacher training. Methods: A systematic scoping literature review combined with a textual narrative synthesis was undertaken. Ten reference databases were searched in May 2020: Academic search premier, CINAHL, Education Research Complete, Humanities International Complete, Psychology and Behavioural Sciences Collection, PsycInfo, Teacher Reference Center, Science Direct, Web of Science and Scopus. Results and Conclusions: Following inclusion/exclusion criteria assessment and screening, 13 articles were included for appraisal and synthesis. Seven papers examined physical simulations, while the remainder examined mixed‐reality simulations. The evidence from this review suggests that simulation, including physical and mixed‐reality types, could be used as a tool to increase confidence, self‐efficacy, classroom management skills and communication. Implications: In comparison to other fields (e.g., nursing, medicine and aviation) simulation in education appears to be in its infancy—more large‐scale research is needed. At the same time, this review indicates that mixed‐reality simulation in particular has the potential for contributing to teacher education, because it offers the potential for learning in various contexts when compared to traditional didactic teaching practices. Lay Description: What is already known about this topic: Computer‐based simulation used in pre‐service teacher training can have a positive impact on specific skills development. The use of virtual reality in relation to pedagogy and pedagogical environments already has a noteworthy evidence‐base, but an overview of physical and mixed‐reality simulations in pre‐service teacher education is underrepresented. Virtual simulation is an emerging powerful tool to provide an inside experience, where pre‐service teachers can engage with the environment and virtual characters in a way that feels real Mixed‐reality simulation involves real and simulated environments in which virtual and real objects, as well as people interact in real time. What this paper adds: An overview of evidence for physical and mixed‐reality simulation used in pre‐service teacher education. Evidence that physical and mixed reality simulation allow trainee‐teachers to reflect on their behaviour within a classroom setting and which is observable by other participants. Implications for practice and/or policy: Educators should explore a range of simulation options in pre‐service teacher education to harness the different strengths of the technologies. In the face of future emergencies, which may reduce face‐to‐face learning contexts, mixed‐reality simulation appears to be a promising approach to instil teaching skills whilst interacting with other participants